Studi Pengembangan Sistem Drainase Perkotaan Berwawasan Lingkungan (Studi Kasus Sub Sistem Drainase Magersari Kota Mojokerto) - Supriyani, Endah; Bisri, M.; Dermawan, Very (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
The purpose of this research is to understand the drainage system, to evaluate the capacity of drainage channel, and to acknowledge the applicable environment-based drainage method. Some data used area rainfall data, population rate, altimetry of channel in location area, land use, inundation and location map.The result of calculation and analysis, the ratio of average absorption area= 0.36, therefore, Magersari sub-drainage system is included within the category without environment-based. Channel capacity, Qs< Q2years, almost all of drainage channel cannot accommodate the discharge. By considering the land limit and the environment preservation principle, therefore, the inundation can be reduced by preparing the injection well method in 1 meter diameter and 3 meters depth, and the retarding basin with dimension 100 x 100 x 3 meter cubic with the filling-up period of 8.79 hours in the catchment area of Afvour Sinoman I.Key words: Drainage, inundation, injection well, retarding basin, environment-based